Endovascular therapies current evidence - Wyatt, Michael G.; Watkinson, A. F. (Tfm Pub., 2006)
As techniques have become established, technology has moved forward at a pace making regular update vital to stay abreast of this expanding speciality. Covering main aspects of vascular disease, this work is useful to specialists who practice endovascular intervention in the fields of interventional radiology, vascular surgery and cardiology.